A CRITICAL APPRAISAL OF HUMAN RESOURCE ACCOUNTING MODELS - Das, Pradip Kumar (PEOPLE: International Journal of Social Sciences, 2018)
Rational use of human resources is vital for taking managerial decisions. Pronouncing qualitatively by dignitaries is the manifestation of the importance of human resources to the prosperity of an organization but very often, quantitative information with regard to their contribution is not recorded in books of accounts and does not find proper place in traditional accounting practices prevalent in India mainly due to inappropriately or insufficiency of their quantification. Human Resource Accounting being an information system considers human resources invested in business as assets and places their monetary values in books of accounts providing valuable information relating to human resources to all interested parties. In a developing country like India with abundant human resources, paying inadequate attention and keeping their contribution outside the financial picture of an organisation evidence the lack of transparency in books of accounts. With the advent of scientific management with emphasis on quantitative methodology to execute the effective utilization of all resources, the study aims at quantifying data relating to human resources and critically examining the models developed so far from the author’s own perception to report its value for the management of organization. The study finds that there is no single model satisfying all the needs of a model. A great deal of further research work relating to application of a system of modified version of human resource accounting is of paramount importance for successful development of human resource.